A Survey of Dental Students on Aligner Orthodontic Therapy: A Questionnaire Based Survey - Aiman Elmabruk,; Abdulghani Alarabi,; Fathi Almadani,; Elhadi Kadoshi, (AlQalam Journal of Medical and Applied Sciences, 2023)
Aims. This survey was conducted to assess the apprehension and awareness among dental students about clear aligner orthodontic therapy. Dental students five Libyan dental faculties were included in this survey. Methods. A web-based survey and questionnaire consisting of 18 questions was prepared and sent to dental students studying at five Libyan dental faculties; Tripoli, Benghazi, Aalasmaria, Alkhomus, and Sebha, through Google Forms. A total of 310 participants completed the survey out of which 44 were males and 262 were females. The sample consisted of fourth grade dental students. Chi-square test of association was used to evaluate the awareness of dental students followed by Cramer’s V test to evaluate the strength of association. Results. The obtained results showed that females were more enlightened about clear aligner therapy than their male peer group. Conclusion. The study concluded that fourth-grade dental students have good knowledge about orthodontic clear aligner therapy, and it was seen that females on average have more awareness about this treatment modality.